Redescription of three species of Apseudidae (Tanaidacea) from the Kurile-Kamchatka Trench with general remarks on tanaidacean diversity in oceanic trenches. - Jóźwiak P. (Journal of the Marine Biological Association of the United Kingdom, 1-19, 2015)
Redescriptions of three species of Apseudidae are given based on samples collected from the Kurile-Kamchatka Trench during the Kurambio deep-sea expedition: Fageapseudes bicornis, F. vitjazi and Leviapseudes zenkevitchi. The identification key for species of Fageapseudes is given. Tanaidacean fauna from the main world trenches is discussed.